2021
DOI: 10.1039/d1cc00582k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the energy barrier and hysteresis temperature in two benchtop-stable Ho(iii) single-ion magnets

Abstract: The energy barrier and hysteresis temperature in two benchtop-stable D5h-symmetry HoIII single-ion magnets were significantly enhanced via the variation of halogen anion. The coexistence of high energy barrier of 418...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The nature of the second coordination sphere of the rare earth center is also a point of importance. For the series of complexes [Dy((Me 2 N) 3 PO) 2 (H 2 O) 5 ] n ·3 n X (X = Cl, n = 1; X = Br, n = 2, and X = I, n = 1; Table 10 entries 7–9), 148,149 [Dy(cy 3 PO) 2 (H 2 O) 5 ]·3X (X = Cl, Br, CF 3 SO 3 , entries 14–16), 150,151 and [Ho(pyr 3 PO) 2 (H 2 O) 5 ]X 3 (X = Cl, Br, entries 12 and 13), 152 where various phosphonic triamides and phosphine oxides act as strong axial ligands and water molecules occupy the equatorial coordination sites of the Ln ions, the value of U eff / k B was found to significantly change with the nature of the anions associated with the complex. Theoretical calculations of the energy barrier ( U cal ) for model molecules derived from the two complexes [Dy((Me 2 N) 3 PO) 2 (H 2 O) 5 ]Cl 3 ·((Me 2 N) 3 PO)·H 2 O and [Dy((Me 2 N) 3 PO) 2 (H 2 O) 5 ]I 3 ·2((Me 2 N) 3 PO), 148,149 showed that moving the second coordination sphere away from the magnetic center ( i.e.…”
Section: Lanthanide Ions With Pentagonal Bipyramidal Coordination Spherementioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the second coordination sphere of the rare earth center is also a point of importance. For the series of complexes [Dy((Me 2 N) 3 PO) 2 (H 2 O) 5 ] n ·3 n X (X = Cl, n = 1; X = Br, n = 2, and X = I, n = 1; Table 10 entries 7–9), 148,149 [Dy(cy 3 PO) 2 (H 2 O) 5 ]·3X (X = Cl, Br, CF 3 SO 3 , entries 14–16), 150,151 and [Ho(pyr 3 PO) 2 (H 2 O) 5 ]X 3 (X = Cl, Br, entries 12 and 13), 152 where various phosphonic triamides and phosphine oxides act as strong axial ligands and water molecules occupy the equatorial coordination sites of the Ln ions, the value of U eff / k B was found to significantly change with the nature of the anions associated with the complex. Theoretical calculations of the energy barrier ( U cal ) for model molecules derived from the two complexes [Dy((Me 2 N) 3 PO) 2 (H 2 O) 5 ]Cl 3 ·((Me 2 N) 3 PO)·H 2 O and [Dy((Me 2 N) 3 PO) 2 (H 2 O) 5 ]I 3 ·2((Me 2 N) 3 PO), 148,149 showed that moving the second coordination sphere away from the magnetic center ( i.e.…”
Section: Lanthanide Ions With Pentagonal Bipyramidal Coordination Spherementioning
confidence: 99%
“…An illustration is given by the two Ho complexes [Ho(pyr 3 PO) 2 (H 2 O) 5 ]Cl 3 and [Ho(pyr 3 PO) 2 (H 2 O) 5 ]Br 3 . 152 The replacement of Cl − by Br − leads to a greater separation between the five equatorially coordinated water molecules and the counter ions (the O eq water ⋯X − distances range from 3.014 to 3.119 with X = Cl − and from 3.182 to 3.262 Å for X = Br − ), which implies a weakening of the H-bond interactions. Concomitantly, the axial Ho–O bond distances are reduced and the axial O–Ho–O angle becomes more linear (entries 12 and 13 in Table 10).…”
Section: Lanthanide Ions With Pentagonal Bipyramidal Coordination Spherementioning
confidence: 99%
“…The discovery of a molecule-based material {Mn 12 Ac} showing magnetic bistability in 1993 , brought an upsurge of research interest in single-molecule magnets (SMMs) for their potential applications in high-density information storage, quantum computing, and molecular spintronic devices. In the past few decades, numerous SMMs with diversified structures have been reported, including mononuclear, dinuclear, multinuclear, and framework-based homometallic and heterometallic complexes, constantly broadening our understandings toward SMMs and promoting progress in this field. Past researches have shown that designing matching crystal fields to the shape of electron density at the ground state of lanthanide metal ions is an efficient way to improve the effective energy barrier ( U eff ) of SMMs and following this rule, many SMMs with high U eff have been reported. However, the blocking temperature ( T B ) of SMM is commonly low because of the occurrence of multiple relaxation processes. The magnetic anisotropy and magnetization dynamics of lanthanide SMMs are very sensitive to the change of molecular structure. Hence, varying assembly conditions of complexes and comparing their crystal structures and magnetic properties is an efficient method to gain important information of magneto-structural relationships, which further contributes to the design and modulation of molecular structures elaborately to achieve high-performance SMMs.…”
Section: Introductionmentioning
confidence: 99%
“…14 The performance of the above Ln-SMMs is improved and they set new records thanks to the crystal field. [15][16][17][18][19] At the same time, they are also excellent in constructing lightweight lanthanide complexes, 20 square-antiprism coordination geometry single-ion magnets 21 and coordination polymer magnetic materials. 22 In addition, some of the nanoscale molecular magnets containing Ln-OvP exhibit magnetodielectric effects, 23 reversible magnetooptical properties, 24 and photomagnetism phenomena.…”
Section: Introductionmentioning
confidence: 99%